A critical approach to ecological urbanism in Hong Kong. Issue 2 (2nd July 2016) - Lorrimar-Shanks, Jennifer; Owen, Ceridwen
Abstract : This paper uses a process of ecological reasoning to challenge normative concepts of sustainable urbanism. Ecological metaphor is often applied in a normative manner, with the assumption that ecologically derived design concepts are wholly positive and 'sustainable'; however, this is not necessarily the case. Through a detailed case study of Hong Kong, we reveal that the interpretive nature of ecological urbanism can produce a variety of outcomes to either contribute to, by explicating and imagining, or undermine sustainability endeavours, by misleading or obscuring. Employing a situated narrative technique we challenge established ecological design concepts, such as 'self-sufficiency' and 'eco-efficiency', with their cultural residuals of individualistic, mechanistic values. In their place, the notion of autopoiesis is proposed, reconceptualising Hong Kong as an interactive network of agents working to regain sovereignty over production, distribution and consumption patterns. The implications of this research demonstrate the importance of criticality, reflexivity and situated engagement in conceiving, communicating and transforming sustainability concepts. We argue that it is this process, rather than the concepts themselves, that underpins the vitality of ecological urbanism.